Organisational cultures : networks, clusters, alliances - Bussmann, Uwe; Panz, Robert Marc; Schweighofer, Silvia (Compact., 2014)
Nowadays, single companies are confronted with great difficulties. The progress of the information technology and the distribution of the Internet as well as the changing demand of customers, especially for no-standardised products force them to react immediately. In order to solve these problems, the companies should work on the following aspects:How can they reach the state of flexibility to meet the changing demand? How can they compete within a market with increasing innovations of products and decreasing product life-cycl? How can they acquire the necessary capital, technology and know-how.